Elicitor-Based Biostimulant PSP1 Protects Soybean Against Late Season Diseases in Field Trials - Chalfoun, Nadia R.; Durman, Sandra B.; González-Montaner, Jorge; Reznikov, Sebastián; De Lisi, Vicente; González, Victoria; Moretti, Enrique R.; Devani, Mario R.; Ploper, L. Daniel; Castagnaro, Atilio P.; Welin, Björn (Frontiers in Plant Science, 2018)
Currently, fungicide application in soybean production accounts for an important amount of global pesticide use, and it is therefore most desirable to find new healthier and more environmental friendly alternatives for the phytosanitary management in this crop. In this study we present convincing evidence for effective induction of disease protection by the agricultural biostimulant PSP1, a formulation based on the plant-defense eliciting activity of the fungal protease AsES (Acremonium strictum elicitor subtilisin), in multiple field trials in Argentina. PSP1 was shown to combine well with commercial spray adjuvants, an insecticide, a herbicide and fungicides used in Argentinian soybean production without losing any defense-inducing activity, indicating an easy and efficient adaptability to conventional soybean production and disease management in the region. Results from multiple soybean field trials conducted with different elite genotypes at several locations during two consecutive growing seasons, showed that PSP1 is able to induce an enhanced pathogen defense which effectively reduced late season disease (LSD) development in field-grown soybean. This defense response seems to be broad-range as disease development was clearly reduced for at least three different fungi causing LSDs in soybean (Septoria glycines, Cercospora kikuchii and Cercospora sojina). It was noteworthy that application of PSP1 in soybean alone gave a similar protection against fungal diseases as compared to the commercial fungicides included in the field trials and that PSP1 applied together with a fungicide at reproductive stages enhanced disease protection and significantly increased grain yields. PSP1 is the first example of an elicitor-based strategy in order to efficiently control multiple fungal diseases under field conditions in the soybean crop. These results show the feasibility of using induced resistance products as complements or even full-good replacements to currently used chemical pesticides, fulfilling a role as important components of a more sustainable crop disease management system.